Karakteristik dan Lingkungan Pengendapan Batubara Formasi Tanjung di daerah Binuang dan sekitarnya, Kalimantan Selatan - Heryanto, R. (Indonesian Journal on Geoscience, 2009)
DOI: 10.17014/ijog.v4i4.84The Tanjung Formation in Binuang and its surrounding area, situated in the eastern margin of the Barito Basin, overlies the Pre - Tertiary rock basement that consists of metamorphic, igneous, volcanic, and sedimentary rocks. The Tanjung Formation, which are Eocene in age, is unconformably overlain by the Plio - Pleistocene Dahor Formation. The Tanjung Formation consists of coarse-grained sandstone and conglomerate in the lower part, mudstone with interbedded coal seams and sandstone in the middle part, and intercalations of mudstone and fine-grained sandstone showing parallel laminations, wavy - lenticular, and flaser beddings, with some interbedded of medium - to coarse-grained sandstones in the upper part. The rock sequence is overlain conformably by the Claystone Member of the Tanjung Formation. Coal seams in the Tanjung Formation are found to be 50 to 350 cm thick. Megascopically, the coal is black, bright to bright banded, black in streak, conchoidal, and light. Petrographic analysis indicates that the vitrinite, in general, develops within the coal seams in all of the zones, whilst inertinite developes in the Eastern Zone (14.2 - 16.0 %). Vitrinite reflectance of coal samples in the Western Zone varies from 0.43 to 0.47 %, in the Middle Zone is 0.45 %, and in the Eastern Zone is 0.45 to 0.50 %. Rank of the coal seams in all of the zones are subbituminous B, according to the ASTM classification. The depositional environment of the coal bearing sedimentary rocks and coal seams in the Western and Middle Zones was a wet forest swamp facies (backmangrove to fresh water swamp) with upper to lower delta plain environment, in a transgressive condition; whereas in the Eastern Zone was a wet forest swamp (fresh water swamp) in a flood plain fasies, and a transgressive condition.